Pengaruh Penggunaan Media Pasir Berwarna dalam Mengembangkan Kreativitas Anak Usia Dini di TK IT Adzkia 2 Padang - Beta Apriani; Sri Hartati (Yayasan Darussalam Bengkulu, 2024)
Creativity is an important component that must be developed in early childhood. In order to develop creativity in early childhood, one strategy that can be used is to use colored sand as a learning medium. This research aims to determine the effect of using colored sand media on the creativity of early childhood at Adzkia Padang Kindergarten. This research was conducted using quantitative methods with a quasi-experimental design. The research was carried out at Adzkia Padang Kindergarten with a sample of class Gaza 1 for the experimental class and class Gaza 2 for the control class. Data collection was carried out through observation with an observation sheet instrument consisting of four assessment indicators. The data analysis techniques used in this research are descriptive statistical analysis and nonparametric analysis using SPSS 27.0 for Windows. Based on the research conducted, the results showed that the use of colored sand media had a significant impact on increasing the creativity of early childhood at Adzkia Padang Kindergarten. This is based on the results of the T Test where the t-hit value was obtained (5.406) with a significance level of (0.000) which means that Ho is rejected and HI is accepted because 0.000 is smaller than 0.025.